Aesthetics of discomfort : conversations on disquieting art - Aldama, Frederick Luis (University of Michigan, 2016)
Preface -- Prologue : scratching at the surface of discomfort -- Digging deeper at a possible theory for an aesthetics of discomfort -- Bottoms up -- Awkward spaces -- Noise to the ears -- Retchful art -- Revolting reels -- Epilogue : now That's disquieting!